Prevalence of persistent primary teeth at the East Selemadeg I Community Health Centre in Tabanan, Bali, from period January 2024 to March 2025: Prevalensi kasus persistensi gigi sulung di UPTD Puskesmas Selemadeg Timur I Tabanan Bali pada periode Januari 2024 hingga Maret 2025 - Molin, Ni Made; Pratama, I Wayan Agus Wirya; Kusumadewi, Ni Wayan Adi; Palguna, I Gede Pandu (Makassar Dental Journal PDGI Makassar, 2025)
Dental health problems can occur in all age groups, especially in children, and it is important to pay attention to them. In addi-tion to caries, another common dental problem in children is persistent primary teeth. This study was conducted at the UPTD Selemadeg Timur I Community Health Centre, Tabanan, Bali, from January to March 2025. This study was conducted using an observational cross-sectional method. Data on patient visits for persistent deciduous teeth at the Selemadeg Timur I Commu-nity Health Centre, involved 359 patients. It was concluded that the high incidence of persistent teeth at the health centre may be due to a lack of knowledge among parents.